Fauna subterrânea de Collembola no Oeste Potiguar : diversidade críptica e novas espécies - Souza, Paolla Gabryelle Cavalcante de (2025)
Integrative taxonomy is essential for identifying and reclassifying Collembola taxa that are morphologically similar. Animals inhabiting caves are subject to similar selective pressures and may exhibit comparable morphological traits, such as reduced eyes and pigmentation, as well as elongated appendages. The genus Trogolaphysa (Entomobryidae, Paronellinae) includes 24 species recorded in Brazil and is widely distributed in caves of the semi-arid region of Rio Grande do Norte (RN). The aim of this study was to identify the species occurring in caves of the midwestern region of RN, their distribution, delimitation, and evolutionary history, through the integration of morphological and molecular data, and, if necessary, to describe them. A species of Trogolaphysa found in RN caves, resembling Lepidonella zeppelinii, was re-evaluated. After reanalysis of the type material of L. zeppelinii, the species was redescribed and transferred to the genus Trogolaphysa, being renamed Trogolaphysa zeppelinii comb. nov. A dataset of 32 partial sequences of Cytochrome Oxidase I (COX1) of T. zeppelinii comb. nov. was used in maximum likelihood and Bayesian inference phylogenetic trees, as well as species delimitation methods. Five lineages of T. zeppelinii comb. nov. were delimited, with two lineages showing absolute support values and similar morphologies. Genetic distance, population analyses, and Mantel tests confirmed the distinction between populations from the northern and southern parts of the studied area. However, the lack of evident morphological differences prevents these populations from being classified as distinct species. Additionally, the extraction and sequencing of the mitogenome of T. zeppelinii comb. nov. were carried out, presenting its complete mitogenome and a phylogenetic tree based on protein-coding genes to verify its phylogenetic placement among Entomobryoidea. Its mitogenome comprises 14,822 base pairs, containing 13 protein-coding genes, 22 transfer RNA genes, and two ribosomal RNA genes. Phylogenetic analysis confirmed that the species belongs to a monophyletic clade of Trogolaphysa within Paronellinae, related to Troglopedetes and Cyphoderus. Phylogenetic analyses with mitogenomes of Neotropical species are important for a better understanding of relationships among genera of Paronellinae. Finally, two new species of Collembola collected in caves of the semi-arid region of Rio Grande do Norte were described: Cyphoderus caatinguensis sp. nov. and Pararrhopalites iataganii sp. nov. C. caatinguensis sp. nov. is distinguished by the combination of its labial chaetotaxy, claws with filamentous apical tooth, and the number of plumose setae on the dorsal side of the dens. P. iataganii sp. nov., in turn, differs from other species of the genus by the number of subsegments in the fourth antennomere, the number of cephalic spines, the chaetotaxy of the manubrium, and the ventral formula of the dens. Both species display troglomorphic traits, such as reduced pigmentation and eyes, and their description contributes to the understanding of Neotropical subterranean fauna and provides support for future conservation policies for caves in the state of Rio Grande do Norte. This study highlights the complexity of the genetic diversity of collembolans in cave ecosystems, reinforcing the need for integrative taxonomic approaches.